Pengaruh Kesadaran Merek Dan Citra Merek Terhadap Keputusan Pembelian Produk AMDK SUMMIT - Apriany, Ade; Gendalasari, Gen Gen; Fadillah, Adil (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The purpose of this research was to determine the factors of brand awareness and brand imager which can affects customer’s buying decisions on AMDK Sumit. This research use independent variables (Brand Awareness and Brand Image) and dependent variable (Buying Decision). It was conducted in Bogor and spread quisioners to 120 citizen to collect the data. It was processed using SPSS program. The results shows that (1) Brand Awareness has no positive and insignificant effect on customer’s Buying Decision at AMDK Summit with a regression coefficent value of 0,039 and a significant value of 0,885. (2) Brand Image has a positive and significant effect on customer’s Buying Decisions at AMDK Summit with a regression coefficent value of 1,015 and a significant value of 0,000. (3) Brand Awareness and Brand Image have a positive and significant effect on customer’s Buying Decisions at AMDK Summit with an F value of 183,549 and greater than the F table of 3,07 with a significant value of 0,000.